Impact of Diabetes Mellitus Type 2 on Clinical Characteristics of Breast Cancer Patients - Mujtaba Hasan Siddiqui, Muhammad Asim Rana, Mohammed Rehan Omar Siddiqui, Waseem Iqbal, Rizwan Elahi, Zahra Nawaz, Muhammad Mansoor Hafeez, (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: To study the impact of type 2 diabetes mellitus on clinical features of breast cancer. Study Design: Cross-sectional, observational study. Place and Duration of Study: Departments of Medicine, Bahria International Hospital and Farooq Hospital Lahore from 1st July 2017 to 1st December 2021. Methodology: Ninety breast cancer patients with diabetes whose clinical characteristics were compared with the control group of non-diabetic breast cancer patients. After confirmation of diabetic status of the patients through evaluation of blood glucose levels, pathological findings including spread of cancerous cells, their size, lymph node involvement, oestrogen receptor (ER), progesterone receptor (PR), and Her-2 status were evaluated. Obesity was declared in patients having body mass index greater than 30. Result: On comparison with control group, no significant difference was found in age and parity status of patients at the time of diagnosis whereas crude comorbidity score was significantly higher in diabetic patients (0.002). Average body mass index score of diabetic patients and those in control group was 30.5 than 23.7 respectively. 32 (33.5%) Diabetic breast cancer patients were declared obese than 26 (17.3%) non-diabetic patients. 82 (54%) of non-diabetic patients were diagnosed at Stage 1 of breast cancer. 93.3% of diabetic patients were found to have invasive ductal cancer (IDC). No significant difference was found in grading and hormonal status of the patients of two groups. Multivariate analyses on adjustment of body mass index found most diabetic patients to be negative for progesterone and oestrogen receptors. Conclusion: Type 2 diabetes mellitus plays an important role in the progression and worsening of prognosis in breast cancer patients. Therefore, it should be considered as an important risk factor during the treatment of tumours including breast cancer. Controlling diabetic complications in breast cancer patients would play a pivotal role improving the clinical outcomes in breast cancer patients. Keywords: Breast cancer, Diabetes mellitus type 2, Tumour progression, Obesity, Body mass index